Impact of SARS-CoV-2 infection (COVID-19) in the treatment of duodenal gunshot injury (Revista Argentina de Cirugía, 2021)
We report the case of a patient with an abdominal gunshot trauma with liver and duodenal injury who underwent pyloric exclusion and liver repair in another institution. The patient was transferred to our institution 12 hours after surgery. During hospitalization, severe pneumonia due to COVID-19 and complications of the initial surgery developed. Non-surgical management was decided due to the severity of the disease. Percutaneous drainage allowed for the management of the collections avoiding a major initial surgery. Once he recovered from the pneumonia, the definite surgery was performed. Severe COVID-19 pneumonia in a patient with serious duodenal shotgun injury is a determining factor for decision-making of treatment options.
Keywords: COVID -19; SARS-Cov-2; gunshot wound; non-operative treatment